THE REASONS OF LANGUAGE SHIFT IN GAYONESE AMONG CHILDREN AT SOUTHEAST ACEH REGENCY - Dina Sartika .; Winda Setiasari .; Anni Holila Pulungan (LINGUISTIK TERAPAN, 2023)
This study aims to find out the reasons of language shift occurs in children at Jambur Damar village Southeast Aceh Regency. The Gayo dialect, the native tongue of Jambur Damar village in Southeast Aceh Regency. This study applied qualitative research method. The study subject were ten children of Jambur Damar village Southeast Aceh Regency. Furthermore, observation, interview and documentation were employed in collecting the data. After collecting the data, it was analyzed by the following stages, transcription, identification and classification. The findings showed that the reasons language shift occurrence in this study were habitual language usage and environment. Meanwhile, environment is one of the reasons that greatly influenced the language shift because it was used to connect with neighbors in the Jambur Damar village who spoke different mother tongues.